Non-Linear Association between Obstructive Sleep Apnea Risk and Lipid Profile: Data from the 2015–2018 National Health and Nutrition Examination Survey - Ge, Gaoyuan; Bo, Dan; Zhang, Fengxiang; Yang, Di (Reviews in cardiovascular medicine, 2024)
Background: The relationship between the multivariable apnea prediction (MAP) index and lipid levels was examined using a cross-sectional and retrospective study of National Health and Nutrition Examination Surveys (2015–2018). A total of 3195 participants with MAP scores were included in the analysis. Methods: The MAP index, an algorithm leveraging sleep apnea symptom frequency, body mass index (BMI), age, and sex, estimates the risk of obstructive sleep apnea (OSA). We investigated the associations between the MAP index and lipid profiles—specifically, high-density lipoprotein cholesterol (HDL-C), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG) —using weighted linear regression and restricted cubic splines (RCS) analysis. Additionally, mediation analysis was conducted to explore the potential mediating role of physical activity on the link between OSA risk, hyperlipidemia, and cardiovascular mortality. Results: A non-linear relationship was observed between OSA severity and lipid profiles, including elevated levels of TC, increased LDL-C, higher TG, and decreased HDL-C (All p for non-linearity <0.05). The findings remained consistent across the stratified sensitivity analyses. Furthermore, physical activity served as a mediator in the association between the MAP index and both hyperlipidemia and cardiovascular mortality, accounting for 16.6% and 16.7% of the indirect effects, respectively. Conclusions: Participants at high risk for OSA demonstrated an increased prevalence of dyslipidemia. Additionally, engagement in physical activity was shown to have beneficial effects on lipid metabolism.